(untitled) (Polish Yearbook of International Law, 2024)
This article addresses the complex issue of immunity for State officials from foreign criminal jurisdiction, with a focus on the ILC’s role in codifying and ensuring the compatibility of international legal acts. It underscores the calls for exceptions to functional immunity, particularly concerning ius cogens norms, and it highlights how the current framework often impedes accountability for international crimes. However, the ILC’s limitation of Art. 7 to immunity ratione materiae, excluding jurisdictional immunities, presents a legislative gap that hampers prosecution under universal jurisdiction. This underscores the need for international codification and progressive development to reconcile immunity doctrines with the imperative of accountability for serious international crimes. The article highlights the lack of a clear international position due to: (1) the absence of uniform definitions for immunity ratione personae, ratione materiae and jurisdictional immunity, (2) the identification of various exceptions limiting the invocation of immunities in domestic and third-State courts and (3) the inconsistent interpretation of immunity exclusions for ius cogens violations. It argues for harmonising legal norms at the international level to adequately initiate and conduct criminal proceedings by specifying the circumstances that exclude jurisdictional, ratione materiae and ratione personae immunities, thus re-establishing criminal accountability for international crimes.